Effects of Ty insertions on HIS4 transcription in Saccharomyces cerevisiae. - Silverman, S J (1984)
Insertion of two different Ty elements into the Saccharomyces cerevisiae HIS4 regulatory region eliminates transcription of HIS4. Transcription can be restored by genetic rearrangements involving the Ty element inserted at HIS4. Several deletions, an inversion, a translocation, and a gene conversion are capable of restoring HIS4 transcription. Some of the rearrangements result in new transcriptional initiation sites. One type of revertant of his4-912 results from recombination between the delta elements flanking the Ty element, leaving a solo delta in place of the complete Ty. Strains carrying a Ty912 delta at HIS4 are His- at 23 degrees C. Unlinked suppressors (SPT) lead to suppression of this His- phenotype and increase levels of the normal HIS4 transcript. These suppressor genes affect not only the amount of transcription from the normal HIS4 initiation site, but also that from new initiation sites within Ty sequences adjacent to HIS4.